Peningkatan Pengetahuan tentang Standarisasi dan Jaminan Halal Pemilihan Bahan Baku UM Savira Frozen Food: Enhancing Knowledge on Standardization and Halal Assurance in Raw Material Selection for UM Savira Frozen Food - Syamsuri, Syamsuri; Rahmawan, Arief; Ahmad, Rusyda Afifah; Umam, Khoirul; Kamaluddin, Imam (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Currently, various products are offered to attract consumer interest, especially in the food industry with fast and practical serving offers. Frozen food is a food choice that is currently growing rapidly in Indonesia, including in Ponorogo Regency. Along with the increasing interest in consuming frozen food, awareness of the halal aspects of products is needed and must be considered by food producers. However, the limitations and understanding of Islamic Sharia standards have not become a principle in running a business. Therefore, the purpose of this community service is in the form of assistance starting from the preparation of training modules, socialization, and introduction of halal concepts, theoretical and practical training, assistance and consultation, and implementation of halal certification. Assistance to UM Savira Frozen Food is focused on understanding how to choose halal raw materials according to halal value chain standards. Through this training, business actors will be given practical knowledge regarding the criteria for halal raw materials, halal verification methods, and the application of halal standards in the entire production process. The results of this activity have a positive impact in terms of knowledge and understanding of partners who are aware of halal standards to ensure that products produced by micro businesses have guaranteed quality and meet halal criteria, providing a sense of security and trust to consumers.